Enhancing the rate performance of spherical LiFeBO3/C via Cr doping. Issue 54 (5th July 2017) - Dong, X. X.; Huang, C. Y.; Jin, Q.; Zhou, J.; Feng, P.; Shi, F. Y.; Zhang, D. Y.
Abstract : Spherical LiFe1− x Cr x BO3 /C ( x = 0, 0.005, 0.008) has been successfully synthesized by ball-milling and spray-drying assisted high-temperature solid-state reaction. Abstract : Spherical LiFe1− x Cr x BO3 /C ( x = 0, 0.005, 0.008) has been successfully synthesized by ball-milling and spray-drying assisted high-temperature solid-state reaction. The effect of Cr doping on LiFeBO3 /C is characterized by XRD, energy-dispersive X-ray spectroscopy (EDS) and XPS. The results show that LiFe0.995 Cr0.005 BO3 /C delivers the highest initial discharge specific capacity of 196.3 mA h g −1 at 0.1C and superior rate capability of 90 mA h g −1 at 5C. Moreover the material presents a cyclic retention of 95% after 50 cycles at 1C. Such improvement in the electrochemical performance can be attributed to the high electronic conductivities (4.75 × 10 −5 S cm −1 ) and Li ion diffusion coefficients (9.20 × 10 −13 cm 2 s −1 ). The introduction of supervalent Cr 3+ into the LiFeBO3 lattice produces Fe vacancies with accompanying conduction electrons, which lead to the enhanced electronic conductivity and Li ion diffusion coefficient.